2017
DOI: 10.1007/s00415-017-8485-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in multiple sclerosis relapse

Abstract: Relapses are a characteristic clinical feature of multiple sclerosis (MS), but an appreciation of factors that cause them remains elusive. In this study, we have examined seasonal variation of relapse in a large population-based MS cohort and correlated observed patterns with age, sex, disease course, and climatic factors. Relapse data were recorded prospectively in 2076 patients between 2005 and 2014. 3902 events were recorded in 1158 patients (range 0–24). There was significant seasonal variation in relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Seasonal changes in air pollutants concentrations, the type of area (e.g., topography, level of traffic etc.) and the seasonal possible individual air pollutant effect on MS activity could explain mixed results concerning seasonal pattern in relapses rate observed in the literature (Harding et al, 2017). We adjusted on holidays since they may influence industrial activities and road traffic but also and particularly the presence of patients at home.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seasonal changes in air pollutants concentrations, the type of area (e.g., topography, level of traffic etc.) and the seasonal possible individual air pollutant effect on MS activity could explain mixed results concerning seasonal pattern in relapses rate observed in the literature (Harding et al, 2017). We adjusted on holidays since they may influence industrial activities and road traffic but also and particularly the presence of patients at home.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, some studies have reported associations between UV level and MS exacerbations (Spelman et al, 2014; Tremlett et al, 2008), suggesting a possible role of erythemal ultraviolet radiation in the production of serum vitamin D production that might influence relapse incidence (Tremlett et al, 2008). However, Harding et al (2017) reported highest risks in early summer when sunshine duration is elevated and lowest risks at the end of summer (Harding et al, 2017), suggesting that vitamin D might not be the only environment factor incriminated in MS relapses (e.g., interactions etc.). Our results seem to corroborate seasonal changes in MS activity, as associations with air pollutants varied across season, so as established or likely confounding variables we accounted in our models (meteorological, infections and allergy variables).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations